2021
DOI: 10.1097/ccm.0000000000005233
|View full text |Cite
|
Sign up to set email alerts
|

Molar Sodium Lactate Attenuates the Severity of Postcardiac Arrest Syndrome: A Preclinical Study

Abstract: To determine whether continuous IV infusion of molar sodium lactate would limit cardiac arrest-induced neurologic injury and cardiovascular failure.DESIGN: Randomized blinded study (animal model). SETTING: University animal research facility.SUBJECTS: Twenty-four adult male "New Zealand White" rabbits. INTERVENTIONS:Anesthetized rabbits underwent 12.5 minutes of asphyxial cardiac arrest and were randomized to receive either normal saline (control group, n = 12) or molar sodium lactate (molar sodium lactate gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
5
5
0
Order By: Relevance
“…Our findings are in line with those from a study by Stevin et al [ 17 ], which showed that the infusion of molar HSL for 120 min in rabbits after ROSC increased the proportion of animals with pupillary reactivity at 2 h, reduced biomarkers of brain injury (astrocyte lysis marker S100β), improved hemodynamics (MAP, cardiac output, and left ventricular surface shortening fraction), and improved brain mitochondrial function. Similar to our results, HSL influenced lactatemia, natremia, and kalemia, and pH increased in HSL-treated animals [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in line with those from a study by Stevin et al [ 17 ], which showed that the infusion of molar HSL for 120 min in rabbits after ROSC increased the proportion of animals with pupillary reactivity at 2 h, reduced biomarkers of brain injury (astrocyte lysis marker S100β), improved hemodynamics (MAP, cardiac output, and left ventricular surface shortening fraction), and improved brain mitochondrial function. Similar to our results, HSL influenced lactatemia, natremia, and kalemia, and pH increased in HSL-treated animals [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with those from a study by Stevin et al [ 17 ], which showed that the infusion of molar HSL for 120 min in rabbits after ROSC increased the proportion of animals with pupillary reactivity at 2 h, reduced biomarkers of brain injury (astrocyte lysis marker S100β), improved hemodynamics (MAP, cardiac output, and left ventricular surface shortening fraction), and improved brain mitochondrial function. Similar to our results, HSL influenced lactatemia, natremia, and kalemia, and pH increased in HSL-treated animals [ 17 ]. However, the rabbits in the study by Stevin et al [ 17 ] were treated with a higher HSL dose than that used in the present study (i.e., 80 µmol/Kg/min vs. 30 µmol/Kg/min) for a shorter period of time (i.e., 2 vs. 12 h), and the origin of CA (i.e., asphyxial vs. electrical) and CPR techniques differed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, inhibition of CypD-dependent PTP opening might increase the rate of ROSC and short-term survival through mechanisms that remains to be determined. Thus, researchers should better investigate other therapeutic approaches (eg, molar sodium lactate 35 ) than trying to optimize pharmacological PTP inhibition for improving outcomes of patients admitted alive to hospital after CA. The increase in the rate of ROSC in CypD À/is a very important finding, because, for many decades, epinephrine has been the only pharmacological option to help to "restart" the heart.…”
Section: Discussionmentioning
confidence: 99%